Sweetness and power : the place of sugar in modern history - Mintz, Sidney Wilfred, 1922- (New York : Penguin Books, 1986)
In this book the author shows how Europeans and Americans transformed sugar from a rare foreign luxury to a commonplace necessity of modern life, and how it changed the history of capitalism and industry. He discusses the production and consumption of sugar, and reveals how closely interwoven are sugar's origins as a "slave" crop grown in Europe's tropical colonies with its use first as an extravagant luxury for the aristocracy, then as a staple of the diet of the new industrial proletariat. Finally, he considers how sugar has altered work patterns, eating habits, and our diet in modern times.
Food, sociality, and sugar -- Production -- Consumption -- Power -- Eating and being.
"Elisabeth Sifton books."
Includes bibliographical references (p. [215]-227) and index.
Keywords: Sugar -- Social aspects -- History; Sugar trade -- Social aspects -- History; History